Simultaneous EEG-fMRI data acquisition during cognitive task - Ahmad, R.F. (IEEE Computer Society, 2014)
Functional Magnetic Resonance Imaging (fMRI) has very high spatial resolution as compared to the Electroencephalography (EEG) which on other hand has very high temporal resolution. The pros and cons of the EEG and fMRI are complementary to each other. Simultaneous EEG-fMRI data recording solve the problem to get high spatial and temporal resolution at the same time to study the brain dynamics in efficient manner. EEG-fMRI integration is a new approach to study human brain activity. Recent developments in MRI compatible EEG equipment made this integration more easy and attractive in cognitive neuroscience. The simultaneous EEG-fMRI data acquisition gives us the better information for all activated areas of the brain to understand the cognitive processes. We developed data acquisition setup for simultaneous EEG-fMRI for cognitive tasks. Also data recording has been done for two healthy participants as a pilot study which will be further continued on other healthy participants as well as on patients. The EEG and fMRI data is pre-processed and artefacts are removed. This combined EEG-fMRI data can be further used in multimodal data integration or data fusion which can give the better results and understanding of the cognitive processes of human brain as compared to analysing EEG and fMRI data separately. Â© 2014 IEEE.